Association between prolonged weekly duty hours and self-study time among residents: a cross-sectional study - Nagasaki, Kazuya; Nishizaki, Yuji; Shinozaki, Tomohiro; Shimizu, Taro; Yamamoto, Yu; Shikino, Kiyoshi; Fukui, Sho; Nishiguchi, Sho; Kurihara, Masaru; Katayama, Kohta; Kobayashi, Hiroyuki; Tokuda, Yasuharu (Postgraduate Medical Journal, 2023)
In 2024, the Japanese government will enforce a maximum 80-hour weekly duty hours (DHs) regulation for medical residents. Although this reduction in weekly DHs could increase the self-study time (SST) of these residents, the relationship between these two variables remains unclear. The aim of the study was to investigate the relationship between the SST and DHs of residents in Japan. In this nationwide cross-sectional study, the subjects were candidates of the General Medicine In-Training Examination in the 2020 academic year. We administered questionnaires and categorically asked questions regarding daily SST and weekly DHs during the training period. To account for hospital variability, proportional odds regression models with generalized estimating equations were used to analyse the association between SST and DHs. Of the surveyed 6117 residents, 32.0% were female, 49.1% were postgraduate year-1 residents, 83.8% were affiliated with community hospitals, and 19.9% worked for ≥80 hours/week. Multivariable analysis revealed that residents working ≥80 hours/week spent more time on self-study than those working 60-70 hours/week. Conversely, residents who worked <50 hours/week spent less time on self-study than those who worked 60-70 hours/week. The factors associated with longer SST were sex, postgraduate year, career aspiration for internal medicine, affiliation with community hospitals, academic involvement, and well-being. Residents with long DHs had longer SSTs than residents with short DHs. Future DH restrictions may not increase but rather decrease resident SST. Effective measures to encourage self-study are required, as DH restrictions may shorten SST.